Pemanfaatan E-Commerce Dalam Upaya Meningkatkan Volume Penjualan Pada Mitra Keripik Pisang Arjuna Di Yosodadi Metro Timur - Ira Vahlia; Nina Lelawati (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
Small industry is a profitable business opportunity. The home industry partner of the banana arjuna chips is the banana chips of the home industry, the pride of Yosodadi Metro Timur Village, Lampung. The crispy chips made available are excellent for the Javanese provinces. But in its production every home industry has a variety of problems that make it impossible for home industries to grow and even go bankrupt because they are unable to keep up with the development of the world of commerce that follows developments that rely heavily on technology. Partners still use product sales manually, ie consumers come directly to partners to buy banana chips. To facilitate partners in the sale of banana chips, assistance is provided in partner communities in managing online marketing management and training in making e-commerce systems online, and conducting online system simulations to support the sales process optimally. To ensure the success of the program, an evaluation will be carried out at each stage of program development. So that the sustainability of the business unit will continue as an activity that can improve the economy of the community in the partner environment and can absorb local labor.